A Case Study of An Aerospace Company: Challenges, Impacts, and Strategies in Procurement and Inventory Integration to Enhance Supply Chain Resilience - Teh, Yi Ling (2024)
Integration of procurement and inventory management is crucial for enhancing operational efficiency and supply chain resilience in aerospace manufacturing. However, there are common issues include misaligned procurement schedules and inventory levels, overstocking, stockouts, increased expenses, and vulnerability to supply chain disruptions. These are worsened by reactive management and lack of real-time data, hindering proactive planning and decision-making. Hence, this study explores the challenges, impacts and strategies of XYZ Aerospace Company in integrating procurement and inventory management. The qualitative research with phenomenological approach has been employed for this research. Through interviews with six respondents conducted between May 27 and June 27, 2024, the research identified significant challenges, including reliance on manual processes, basic ERP systems, multiple approval stages in procurement department, and visibility issues in inventory management department. These challenges are prevalent among SMEs in various industries that resulting in inefficiencies such as delayed response times, overstocking, stockouts, and production delays. In contrast, larger corporations and industries such as automotive and consumer electronics have embraced advanced systems like Just-In-Time (JIT) manufacturing and sophisticated ERP systems, thereby improving responsiveness and operational efficiency. XYZ Aerospace Company has implemented strategies to improve resilience, such as better supplier relationship management and development of crisis management team. However, further investments in new technologies, clear communication protocols, and regular audits are needed for substantial improvement. In overall, this study provides insights into integration challenges and suggests strategies that emphasize the importance of best practices for enhancing supply chain resilience.